Cross-sectional study of anxiety symptoms and self-report of awake and sleep bruxism in female TMD patients. Issue 6 (1st November 2016) - Tavares, Luisa Maria Faria; da Silva Parente Macedo, Leonora Cristina; Duarte, Cristina Maria Rabelais; de Goffredo Filho, Gilberto Senechal; de Souza Tesch, Ricardo
Abstract: Aims: The aim of this study was to assess the relationship between levels of anxiety symptoms and prevalence of self-report of awake and sleep bruxism in patients with temporomandibular disorders (TMD). Method: One hundred and eighty-one female patients, aged 19–77 years, were consecutively evaluated. The patients were selected from among those who sought treatment at the TMD and Orofacial Pain Outpatient Clinic of the Petrópolis School of Medicine. All patients completed the questionnaire and underwent clinical examination, both components of the RDC/TMD, in addition to answering questions pertaining to the assessment of levels of anxiety symptoms, taken from the Symptom Check List 90 self-report instrument. The subjects were classified according to the presence of self-reported only awake bruxism, only sleep bruxism, both, or none. A logistic regression procedure was performed to evaluate the possible association through odds ratio between anxiety symptoms and self-reported awake or sleep bruxism. The cofactors for each outcome were age, self-reported bruxism during the circadian period other than the one being evaluated, and the use of selective serotonin reuptake inhibitors. Results: It was possible to demonstrate the presence of a positive and statistically significant relationship between anxiety levels and self-reported awake bruxism. This finding was not observed in those subjects who reported sleep bruxism. Conclusions: A positive relationship was found between self-reported awake bruxism and levels of anxiety symptoms, but not between sleep bruxism and anxiety.